Microstrain distributions in polycrystalline thin film measured by X-ray microdiffraction - Wilkinson, A; Schäfer, N; Chahine, G; Schmid, T; Rissom, T; Schülli, T; Abou-Ras, D (International Union of Crystallography, 2016)
Microstrain distributions were acquired in functional thin films by high resolution X-ray microdiffraction measurements, using a polycrystalline CuInSe2 thin film as model system. This technique not only provides spatial resolutions at the submicrometer scale but also allows for analysis of thin films buried within a complete solar-cell stack. The microstrain values within individual CuInSe2 grains were determined to be in the order of 10-4. These values confirmed corresponding microstrain distribution maps obtained on the same CuInSe2 layer by electron backscatter diffraction and Raman microspectroscopy.